ALLOCATION OF SOFTWARE DESIGN BUILD BRIQUETTE COAL DIRECTORATE IN COAL - Dian Puspasari; Eko Hadiyanto, SSi, MM (Jurnal Sistem Informasi, 1998)
Draft Software Build Coal Briquettes allocator is very important. This will be useful to know the minimum amount needed in allocating coal briquettes from factory to consumer. To simplify the calculations, then use a tool such as computer programs that can provide useful information for analysis and decision making further.